The drag coefficient variations across different speeds in able-bodied, transradial and transtibial amputee cyclists by numerical simulations - Forte, Pedro (2023)
Drag crisis has been described as a drop in the drag coefficient (Cd). This procedure was lately assessed in able-bodied cyclists in time trial position by computational fluid dynamics (CFD). Therefore, the aim of this study was to assess the phenomenon of the drag crisis by computer fluid dynamics in transradial and transtibial amputee cyclists in the upright position. A male elite-level cyclist was recruited for this research. The subject was scanned (3D geometry with a 3D Scan) with his competition bicycle, helmet, suit, and shoes. Consequently, transradial and transtibial 3D models were created editing the able-bodied 3D model. To perform the CFD analyses, a domain measuring 7 x 2.5 x 2.5 m (length, width and height, respectively) was created around each bicycle-cyclist model. The domains were meshed with more than 42 million elements. Numerical simulations by CFD were performed in fluent numerical for speeds between 1 m/s and 13 m/s, with increments of 1 m/s. The total Cd decreased with speed. It ranged from 0.84 to 0.55 in the able-bodied, 0.86 to 0.64 in the transradial and 0.90 to 0.61 in the transtibial. The drag crisis phenomenon was observed between 1m/s and 4m/s in all models.